Simulasi Pendeteksi Kebakaran Dini Menggunakan Cisco Packet Tracer - Cornelia, Noni; Apriliansyah, Muhammad (Jurnal Inovasi Teknologi Terapan, 2025)
This study aims to simulate an early fire detection system based on the Internet of Things (IoT) using Cisco Packet Tracer software. The system is designed by integrating a smoke detector, automatic sprinkler, and siren, all connected through a Home Gateway and monitored via a laptop. When the smoke sensor detects smoke, the system automatically activates the sprinkler and siren, and sends a notification to the monitoring center. Several simulation scenarios were conducted to evaluate the system's reliability and response time. The results indicate that the system operates automatically and responsively according to the implemented programming logic. The use of Cisco Packet Tracer allows system development and testing without the need for physical hardware, thus supporting IoT-based learning and research effectively.